Multiparameter quantitative histological MRI values in high-grade gliomas: a potential biomarker of tumor progression. Issue 6 (15th August 2020) - Reuter, Gilles; Lommers, Emilie; Balteau, Evelyne; Simon, Jessica; Phillips, Christophe; Scholtes, Felix; Martin, Didier; Lombard, Arnaud; Maquet, Pierre
Abstract: Background: Conventional MRI poorly distinguishes brain parenchyma microscopically invaded by high-grade gliomas (HGGs) from the normal brain. By contrast, quantitative histological MRI (hMRI) measures brain microstructure in terms of physical MR parameters influenced by histochemical tissue composition. We aimed to determine the relationship between hMRI parameters in the area surrounding the surgical cavity and the presence of HGG recurrence. Methods: Patients were scanned after surgery with an hMRI multiparameter protocol that allowed for estimations of longitudinal relaxation rate (R1) = 1/T1, effective transverse relaxation rate (R2)*=1/T2*, magnetization transfer saturation (MTsat ), and proton density. The initial perioperative zone (IPZ) was segmented on the postoperative MRI. Once recurrence appeared on conventional MRI, the area of relapsing disease was delineated (extension zone, EZ). Conventional MRI showing recurrence and hMRI were coregistered, allowing for the extraction of parameters R1, R2*, MTsat, and PD in 3 areas: the overlap area between the IPZ and EZ (OZ), the peritumoral brain zone, PBZ (PBZ = IPZ – OZ), and the area of recurrence (RZ = EZ – OZ). Results: Thirty-one patients with HGG who underwent gross-total resection were enrolled. MTsat and R1 were the most strongly associated with tumor progression. MTsat was significantly lower in the OZ and RZ, compared to PBZ. R1 was significantly lower in RZ compared to PBZ. PD was significantly higher in OZ compared to PBZ, and R2* was higher in OZ compared to PBZ or RZ. These changes were detected 4 to 120 weeks before recurrence recognition on conventional MRI. Conclusions: HGG recurrence was associated with hMRI parameters' variation after initial surgery, weeks to months before overt recurrence.